(untitled) (Research, Society and Development, 2020)
The aim of this study is examine the influence of Moodle-based e-learning learning to improve learning outcomes of cadets on the basic material of pneumatic systems. Method used in this study is research and development design. Subject of research was the fourth semester cadets majoring in electro navigation at Surabaya Merchant Marine Polytechnic which was determined by convenience sampling. The data taken from the feasibility in terms of material and media through questionnaires, learning outcomes through pre-test and post-test, as well as students and teacher responses through questionnaires. Expert responses show that Moodle-based e-learning is feasible in terms of media and feasible in terms of material. Learning outcomes in large-scale trials indicate that the results of student questionnaire responses to small-scale and large-scale trials indicate that the majority of students give positive responses to learning activities using Moodle-based e-learning media. Lecturer responses based on the results of the questionnaire showed that lecturers were interested in learning using Moodle-based e-learning learning media that had been applied. Based on the results of the analysis and discussion it can be concluded that Moodle-based e-learning is feasible and effectively applied to the basic material of pneumatic systems. Learning by e-learning has a significant impact on improving the learning outcomes of cadets.